José de la Riva Agüero y Felipe Sassone: Dos pensadores sociales y el fascismo en el Perú - Gonzales Alvarado, Osmar (2020)
During the first third of the 20th century, the conservative sectors were involved in the intellectual discussion of national affairs. Among different ideas, these sectors came to embraced Fascism, the totalitarian ideology from the interwar period in Europe. This article analyzes the career and thoughts of two prominent scholars from the era who were seduced by Fascism: historian José de la Riva Agüero and playwright Felipe Sassone. It also examines the significance of the distance –physical and/or mental– from their country, to think of a Peru that seemed alien to them, and doing so from a visibly foreign perspective to the national reality and social dynamics in the 1930s. At the end, these two ways of conceiving Fascism revealed the intellectual inability from a sector to understand their country, and led to their exclusion from the political debate.